Neonatal herpes simplex. - Garofalo, L. (European Journal of Pediatric Dermatology, 2012)
A 9-day-old baby girl was first observed due to the presence of pustular lesions of the trunk and upper limbs simultaneously appeared 2 days before. The baby was born at term with normal delivery and was in good condition and apyretic. The physical examination (Fig. 1, 2) highlighted about forty pustules with cluster outline distributed on the upper trunk and right elbow. Her mother reported varicella during childhood and her father suffered from herpes simplex labialis and the last episode had occurred a week before. The real-time PCR on a swab from pustule showed intense positivity for HSV-1, while was negative for HSV2 and VVZ. Eye, throat and serum swab were negative for HSV1. The serology showed IgG but no IgM anti-HSV-1 in the mother, who had not Ig against HSV-2, and IgM-HSV-1 in the newborn leading to the final diagnosis of neonatal herpes simplex due to HSV1. The newborn received acyclovir orally (40 mg/kg per day for 6 days).